PENDIDIKAN ISLAM DI TENGAH ARUS GLOBALISASI: PERGESERAN ORIENTASI KEBIJAKAN DAN TANTANGAN NILAI - Adrian Maulana; Sabran; Sri Susmiyati (LPPM Sekolah Tinggi Ilmu Tarbiyah Al Marhalah Al Ulya Bekasi, Indonesia, 2026)
Globalization has emerged as a structural force influencing educational policy directions, including within Islamic education. Global dynamics introduce demands for standardization, competency development, and technological integration, which contribute to shifts in educational orientation. This study aims to analyze the impact of globalization on the shifting orientation of Islamic education policy and its implications for educational values. The research employs a qualitative approach using library research methods through conceptual analysis of academic literature and educational policy discourse. The findings indicate that globalization drives a transformation in Islamic education from value-based orientation toward competency- and performance-based frameworks. This shift leads to the marginalization of moral and spiritual dimensions and creates a dilemma between maintaining value-based identity and responding to global demands. In this context, globalization presents both opportunities for modernization and risks of value reduction. Therefore, Islamic education requires a selective and integrative approach that maintains values as its foundation while developing competencies to remain relevant in the global era.